Spanish Translations and Interpretations of Hamlet’s Soliloquy ‘To Be or not to Be - Manrique Sastre, Carlos (Journal of Artistic Creation and Literary Research, 2025)
To be, or not to be. To act, or not to act. To exist, or not to exist. To understand, or not to understand. To accept, or not to accept… What is the question? Which are the secrets beneath Shakespeare’s famous soliloquy? How was it translated into Spanish? Where these translations accurate, or did they destroy Shakespeare’s deep poetry? A first analysis of the meanings enclosed in the soliloquy will introduce the reader into the soul of the famous speech. When was it written and which literary figures appear are some of the questions whose answers serve as a preparation for the next step: the comparison of the original soliloquy to the Spanish translations. In this paper, several translations, some of them from more than two hundred years ago, are analyzed and compared with one and other and with the original. The last part of the study deals with adaptations of the text to the big screen. Most of the movies cut or adapted the text, but all of them included the famous soliloquy. The rhythm, the movements, the use of objects and the environment around Hamlet are semiotically taken into account in the final part of the paper.